Comment on Karthikeyan et al. Concordance between In Vitro and In Vivo Relative Toxic Potencies of Diesel Exhaust Particles from Different Biodiesel Blends. Toxics 2024, 12, 290 - Katherine R. Landwehr; Alexander N. Larcombe (Toxics)
Biodiesel exhaust toxicology is a difficult field of study, for which there is a paucity of literature, despite decades of research into the subject [...]